PERBANDINGAN TEORI ASURANSI: STUDI PERBANDINGAN TEORI EKONOMI TAQIYYUDDÎN AL-NABANI DAN THOMAS ROBERT MALTUS - Deni Kamaludin Yusup (Asy-Syari'ah, 2014)
Insurance could be understood as a guarantee or a trade given the insurer (insurance company) to the insured for the risk of loss specified in the agreement (polis) with the obligations of the insured have should pay a premium to the insurer (insurance company). In modern times, the insurance is one of profitable transactions, because many people are starting to realize that the insurance is very important thing. This article will explain some of the theories about the insurance from the perspective of Shari'ah and conventional which focused on the economic theory presented by Taqiyyuddîn Al-Nabani and Thomas Robert Maltus. From this article, we are expected to understand about the differences between the concepts of insurance based on shariah and conventional perspektive clearly and thoroughly.